2000
DOI: 10.2460/ajvr.2000.61.1062
|View full text |Cite
|
Sign up to set email alerts
|

Association between infection of the respiratory tract attributable to bovine coronavirus and health and growth performance of cattle in feedlots

Abstract: Bovine coronavirus infects feedlot cattle and is associated with an increased risk for cattle developing respiratory tract disease and pulmonary lesions. Development of appropriate control measures could help reduce the incidence of respiratory tract disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 12 publications
8
81
0
1
Order By: Relevance
“…The BCoV respiratory disease has been described in different areas worldwide, including the United States, 14,19,23 Canada, 8 Turkey, 13 Japan, 17 Finland, 1 and Sweden. 11 In the Finland study, 1 various microorganisms were detected in association with BCoV, including mycoplasmas (mainly Mycoplasma bovis and Mycoplasma dispar), Pasteurella multocida, Mannheimia haemolytica, and Arcanobacterium pyogenes, as well as other viral pathogens, specifically, BPIV3, BRSV, and bovine adenoviruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BCoV respiratory disease has been described in different areas worldwide, including the United States, 14,19,23 Canada, 8 Turkey, 13 Japan, 17 Finland, 1 and Sweden. 11 In the Finland study, 1 various microorganisms were detected in association with BCoV, including mycoplasmas (mainly Mycoplasma bovis and Mycoplasma dispar), Pasteurella multocida, Mannheimia haemolytica, and Arcanobacterium pyogenes, as well as other viral pathogens, specifically, BPIV3, BRSV, and bovine adenoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…4,20 Subsequently, BCoV was also associated with the occurrence of respiratory distress in calves and adults. 19,22 The respiratory syndrome is often observed during or after transportation because the shipping of cattle represents a stressing factor that may facilitate the onset of BCoV-induced respiratory disease, mainly in feedlot calves. The present study reports the results of molecular investigations on outbreaks of respiratory disease due to BCoV infection in Italian cattle herds.…”
Section: Introductionmentioning
confidence: 99%
“…Serological testing for BoCV antibodies was not performed as part of the study reported herein due to a lack of a commercially available test kit. However, animals with BoCV in their nasal swabs tend to have low serological titers for BoCV antibodies, 32,54,71 and low antibody titers at feedlot entry are associated with an increased likelihood of developing clinical respiratory disease 38,53,71 and requiring treatment for respiratory disease. 27,54 It is therefore likely that live export cattle that are shedding BoCV on entry to the assembly depot will have low antibody titers and will thus be more likely to develop and require treatment for respiratory disease during voyages than animals without BoCV in their nasal secretions.…”
Section: 33mentioning
confidence: 99%
“…The presence of BoCV in nasal secretions has been linked to increased odds of death due to BRD during live export voyages, 47 and an increased risk of treatment for respiratory disease, 27,38,54 reduced weight gain, 71 and increased incidence of pulmonary lesions at slaughter 38 in feedlot cattle. Serological testing for BoCV antibodies was not performed as part of the study reported herein due to a lack of a commercially available test kit.…”
Section: 33mentioning
confidence: 99%
“…They are enveloped viruses with a positive-sense single-stranded RNA genome and chiefly infect the upper respiratory and gastrointestinal tract of mammals and birds (7). Coronaviruses also cause a spectrum of diseases in farm animals and domesticated pets, some of which can be dangerous and are a risk to the farming industry (8)(9)(10)(11)(12). Only 4 bovine coronavirus isolates have been fully sequenced and, hence, the knowledge about the genetics of the virus is still insufficient (13).…”
Section: Introductionmentioning
confidence: 99%